Prediction of flourishing based on the components of human psychological flourishing model (HPFM) - hiwa mohamadjani; Mohammad rezaei; Ali Mohammadyfar; Hanieh Hojabrian (مجله علوم روانشناختی, 2021)
Background: Numerous studies have examined flourishing. However, research to assess the validity of the flourishing pattern in the indigenous context of Iran and to address the shortcomings of this model, including the lack of tools to measure some of the components and relationships between the components of the model, has been neglected. Aims: The goal was to predict flourishing based on pattern of psychological flourishing on HPMF human. Method: The research was correlational, the primary teachers of Saqqez were statistical society. 614 people randomly were chosen as sample by multi-step in categories and they responded questionnaire of rehabilitation Riff psychological(1995), Luthans psychological capital(2007), Goldberg five factor personality model(1999), private self awarenesn by Charles Carver(1990), Ahwaz stubbornness psychological AHI(1998), Hozhbaryan flourishing HPFS(2014) and two questionnaire of researcher made on environmental-social-cultural conditions and motivation to flourish(p< 0/01). Results: The result showed that between all variables of the model, there's a positive correlation. The result of structural equations model showed that having purpose will directly meaningfully have positive effects on motivation flourishing. Variables of motivation flourishing, background conditions، intermediate conditions will directly affect self management and indirectly affect positive on flourishing (with interference of self management) Variable of self management also directly influences the flourishing meaningfully. Conclusions: Based on current research, applying enough plans in order to increase conclusion, improvement of background conditions and intermediate conditions, promote flourishing motivation and self management are suggested for flourishing teachers.